2015
DOI: 10.1038/ng.3375
|View full text |Cite
|
Sign up to set email alerts
|

Genomic spectra of biliary tract cancer

Abstract: The incidence of biliary tract cancer (BTC), including intrahepatic (ICC) and extrahepatic (ECC) cholangiocarcinoma and gallbladder cancer, has increased globally; however, no effective targeted molecular therapies have been approved at the present time. Here we molecularly characterized 260 BTCs and uncovered spectra of genomic alterations that included new potential therapeutic targets. Gradient spectra of mutational signatures with a higher burden of the APOBEC-associated mutation signature were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

73
1,086
13
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 977 publications
(1,185 citation statements)
references
References 43 publications
73
1,086
13
13
Order By: Relevance
“…In addition to mutations, K‐Ras gene amplifications occur in a subset of cholangiocarcinomas (Nakamura et al ., 2015). We therefore determined the K‐Ras amplification status of each cell line by qPCR, identifying three amplified lines (SNU‐245, SNU‐1196 and NOZ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to mutations, K‐Ras gene amplifications occur in a subset of cholangiocarcinomas (Nakamura et al ., 2015). We therefore determined the K‐Ras amplification status of each cell line by qPCR, identifying three amplified lines (SNU‐245, SNU‐1196 and NOZ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While K‐Ras mutations and amplifications do occur in primary BTC, the collective frequency of these events in the cell line panel (45%) is significantly greater than that observed in primary cancers (18%) (Nakamura et al ., 2015), suggesting that tumours harbouring these genetic alterations may be more amenable to cell line generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, HCV-related diseases show an increased associ ation with CCA in Europe and other Western countries; the association with HBV is more statistically significant where the prevalence of HBV infection is high, including Asian countries 27,28 . Occult HBV infection is an emerging risk factor for iCCA 29 . The increased incidence of iCCA, registered at the end of the past century, has been linked with the burden of HCV infection 29,30 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recent next-generation sequencing technology has enabled comprehensive mutational profiling of CC and has shown that the mutational spectrum differs according to anatomical subtype and underlying etiology (3,4). In the embryonic stage, the extrahepatic bile duct (EHBD) develops from the embryonic hepatic diverticulum, whereas the intrahepatic bile duct (IHBD) originates within the liver from the ductal plate (5).…”
mentioning
confidence: 99%